2021
DOI: 10.1088/1755-1315/751/1/012133
|View full text |Cite
|
Sign up to set email alerts
|

The leasing development tools in the construction industry of the Russian Federation

Abstract: The article deals with the need for leasing financing of construction organizations aimed to modernize, restore and purchase construction equipment. The importance of leasing in the construction industry of the Russian Federation is revealed. The coefficients of renewal and liquidation and the degree of depreciation of fixed assets are determined. The share of construction machinery and equipment in the structure of the leasing market is presented for the last two years. An important task is to lease objects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, in times of crisis it gets even more deteriorated. Organizations react to crises in various manners, however, medium and small-sized businesses are hit the most (Shastitko & Ménard, 2017;Barykina & Chernykh, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in times of crisis it gets even more deteriorated. Organizations react to crises in various manners, however, medium and small-sized businesses are hit the most (Shastitko & Ménard, 2017;Barykina & Chernykh, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, competition, and the extension of special circumstances and offers for transactions concluding is expanding, and also there emerge issues in the mentioned arena needed to be organized and determined for entities to make more informed decisions in the prevailing era. As a consequence, the examination of the features and specifics of the market of leasing seems highly relevant (Barykina & Chernykh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an operating lease does not have an option right to purchase the leased object. From the definition above, it can be concluded that a lease is a rental contract or agreement (Barykina & Chernykh, 2021). According to Nechaev et al, (2022) the object of the lease is capital goods and the lessee has option rights with a price based on the residual value.…”
Section: Theoritical Review Financing Company (Leasing)mentioning
confidence: 99%